Guidance for establishing crisis standards of care for use in disaster situations : a letter report - Altevogt, Bruce M. (Online access: National Academy of Sciences National Academies Press., 2009)
This report focuses on articulating current concepts and guidance that can assist state and local public health officials, health care facilities, and professionals in the development of systematic and comprehensive policies and protocols for crisis standards of care in disasters where resources are scarce, as well as provide guidance to clinicians, health care institutions, and state and local public health officials for how those crisis standards of care should be implemented in a disaster situation.